Screening of Salinity Tolerance of Twenty Rice Genotypes at the Seedling Stage Through Hydroponic and Ssr Marker (Research in Agriculture Livestock and Fisheries, 2021)
Salinity is one of the major abiotic stresses which severely affect the production of crops across the world. In this experiment, we examined 20 rice genotypes of diverse origins and sources including few salt tolerant varieties (Binadhan-8, Binadhan-10, Pokkali and FL478) as check. The main objective of this study was to determine salt tolerance at seedling stage and to evaluate genetic variation using SSR markers. IRRI standard protocol was applied to screen out salinity among those varieties, at the glasshouse of Bangladesh Institute of Nuclear Agriculture, BAU campus, Mymensingh-2202. Shoot length, root length and total dry matter were recorded at 6dS/m, 8dS/m, 10dS/m and 12 dS/m salt stress levels. According to the morphological and molecular survey of 20 rice genotypes at the seedling stage it was evident that, Binadhan-8, Binadhan-10, Pokkali, FL478, IR64, IR4630, FR13A and Sadamota identified as salt tolerant whereas THDB, Moulata, MV-20, CPD-23, CPD-29, Pot-18, Pot-27 and Dudkalam those were found as susceptible, BRRI dhan67, Binadhan-17 and Binadhan-21 those were traced as highly susceptible. The highest Nei’s genetic distance value 1.0 was found in Moulata vs Sadamota and the lowest value 0.08 was observed in Binadhan-21 vs IR64. It will be used in future breeding program to develop a saline tolerant variety of rice.Res. Agric., Livest. Fish.8(1): 75-88, April 2021